The effect of applying potassium chloride solutions at atmospheric pressure on the sensitivity of dentine in man - Noparatkailas S. (2014)
Objective: To determine the effects of applying KCl solutions to exposed dentine at atmospheric pressure on pain evoked by probing and air blast stimuli in human subjects. Design: The experiments were carried out on 24 premolars in 16 subjects (aged 16-30 years). A cavity (diameter 3 mm, depth 3 mm) was cut at the tip of the buccal cusp and etched with 35% orthophosphoric acid. The cavity was filled with 500, 250 mmol/l KCl or 500 mmol/l NaCl for 10 min, after which it was rinsed with normal saline. Each solution was tested in 8 teeth. Air blast and probing stimuli were applied to the exposed dentine prior to dentine treatment and at 0, 2, 5, 10, and 20 min after treatment. After each stimulus the subject indicated the intensity of the pain evoked on a visual analogue scale (VAS). Results: In teeth treated with 250 or 500 mmol/l KCl, the mean VAS response to air blast stimuli was significantly decreased at 5 and 10 min after treatment. The mean VAS response to probing was significantly decreased 10 min after treatment with 500 mmol/l KCl. Otherwise there were no significant changes. Conclusion: Topical application to exposed dentine of solutions containing a high concentration of potassium ions at atmospheric pressure produce a temporary reduction in the sensitivity of dentine to air blast and probing stimuli. © 2008 Elsevier Ltd. All rights reserved.